Immediate Early Response Gene X-1 (IEX-1) Mediates Ischemic Preconditioning-Induced Cardioprotection in Rats. (29th October 2017) - Xu, Ming-Jiang; Cai, Yan; Qu, Aijuan; Shyy, John Y.-J.; Li, Wenjing; Wang, Xian
Abstract : Reversible myocardial ischemia/reperfusion (I/R) or ischemic preconditioning (IPC) is associated with an immediate genomic response; IPC-induced immediate early genes are associated with reduced infarct size. Because the immediate early response gene X-1 (IEX-1) plays a central role in cell apoptosis, we examine whether IEX-1 exerts protective effects against I/R injury. We found that the IEX-1 mRNA level was increased in the IPC-imposed rat heart. However, it was downregulated in the I/R rat heart, which was prevented by in situ IPC. When IEX-1 was knocked down, the protective effects imposed by IPC were lessened. Local gene delivery of Ad-IEX-1 to the left ventricle greatly diminished cardiac infarct size and improved systolic functions of I/R hearts in rats. In contrast, knocking down IEX-1 expression exacerbates myocardial infarction. Overexpression of IEX-1 in neonatal rat cardiomyocytes significantly reduced hypoxia-reoxygenation-induced intracellular and mitochondrial ROS accumulation and cell apoptosis. Furthermore, IPC-induced phosphorylation and particle translocation of PKCε were impaired by knocking down IEX-1 in vivo, and overexpressing IEX-1 showed similar cardioprotection imposed by IPC. Our results demonstrate that IPC increases IEX-1 expression, which may promote phosphorylation and particle translocation of PKCε and thus reduce intracellular ROS accumulation. These beneficial effects reduce cardiomyocyte apoptosis and necrosis to alleviate cardiac infarction.